An overview and critique of the (TVPS-4) - Ted Brown; Lisa Peres (SAGE Publishing, 2018)
Introduction The Test of Visual Perception Skills - fourth edition (TVPS-4) is an updated version of the Test of Visual Perception Skills - third edition (TVPS-3). The TVPS-4 is a standardized assessment of motor-free visual perception skills for individuals aged 5-21 years. Test norms were derived from a normative sample that reflected the United States population. Method The present paper outlines and appraises the reliability and validity of the TVPS-4. Measurement properties of the TVPS-4 were critiqued using the Quality Criteria for Health Status Questionnaires (QCHSQ) and the Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN) checklist with 4-point rating scale. Results The TVPS-4 manual reports details of reasonable levels and types of overall reliability and validity. The QCHSQ and COSMIN checklist reviews suggested that further research is needed in relation to the TVPS-4's measurement error, reproducibility, internal consistency and cross-cultural validity. Conclusion The TVPS-4 is an in-depth assessment that can be used to identify areas of impairment and assist with goal setting and intervention planning. The impact of the TVPS-4 on occupational therapy practice is also considered. Future research could investigate the cross-cultural validity of the TVPS-4 so that it can be used in other countries with confidence.